2007
DOI: 10.1371/journal.pmed.0040076
|View full text |Cite
|
Sign up to set email alerts
|

Calorie Restriction Increases Muscle Mitochondrial Biogenesis in Healthy Humans

Abstract: BackgroundCaloric restriction without malnutrition extends life span in a range of organisms including insects and mammals and lowers free radical production by the mitochondria. However, the mechanism responsible for this adaptation are poorly understood.Methods and FindingsThe current study was undertaken to examine muscle mitochondrial bioenergetics in response to caloric restriction alone or in combination with exercise in 36 young (36.8 ± 1.0 y), overweight (body mass index, 27.8 ± 0.7 kg/m2) individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
504
3
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 697 publications
(546 citation statements)
references
References 67 publications
27
504
3
3
Order By: Relevance
“…Calorie restricted rodents have a longer lifespan than their ad libitum fed counterparts (85). A recent human trial showed that caloric restriction resulted in the expected reduction in body weight and blood insulin (86). Molecular analysis of this study revealed that caloric restriction and exercise increased the expression of genes involved in nutrient sensing and mitochondrial biogenesis.…”
Section: Mitochondrial Dna Repair and Agingmentioning
confidence: 63%
See 1 more Smart Citation
“…Calorie restricted rodents have a longer lifespan than their ad libitum fed counterparts (85). A recent human trial showed that caloric restriction resulted in the expected reduction in body weight and blood insulin (86). Molecular analysis of this study revealed that caloric restriction and exercise increased the expression of genes involved in nutrient sensing and mitochondrial biogenesis.…”
Section: Mitochondrial Dna Repair and Agingmentioning
confidence: 63%
“…Concurrently, caloric restriction decreased markers of oxidative stress. The authors suggest that caloric restriction induces biogenesis of "efficient" mitochondria as an adaptive mechanism, which in turn lowers oxidative stress (86). Dietary restriction has also been shown to be a modulator of membrane lipid peroxidation and cytosolic antioxidant status (87).…”
Section: Mitochondrial Dna Repair and Agingmentioning
confidence: 99%
“…Increases in mitochondrial biogenesis and function have previously been shown to improve insulin sensitivity (Bonnard et al., 2008; Joseph, Adhihetty, & Leeuwenburgh, 2016). Furthermore, caloric restriction (CR), which is currently the only nutritional intervention that delays aging and extends lifespan in mammals, is known to stimulate mitochondrial metabolism (Civitarese et al., 2007; Lopez‐Lluch et al., 2006). Thus, we investigated the impacts of increased mitochondrial NAD levels on energy metabolism in Nmnat3 Tg mice.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, mitochondria are a major source of free radicals including ROS, and it is accepted that mitochondrial dysfunction contributes considerably to the aging process (Bratic & Larsson, 2013; Murphy, 2009). It has also been shown that CR increases numbers of healthy mitochondria and promotes ATP production in rodents and humans (Civitarese et al., 2007). In addition, CR led to reduced oxygen consumption in mice, but efficient ATP production was maintained with decreased ROS generation (Guarente, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects on glucoregulatory functions, improved insulin sensitivity have been seen in rodents and rhesus monkeys [5,6]. Studies have shown the effects of reduced caloric intake with a cut down on calories by 20-25 % of ad libitum fed subjects [7,8]. A few studies have reduced the intake by a fixed number of calories rather than a percentage of the regular intake.…”
Section: Introductionmentioning
confidence: 99%